The Development of Practical Self-Defense Training for Bullying Prevention for Women Aged 15–25 Years in Dharmasraya Regency - Fitri, Alchonity Harika; Sukron, Muhammad; Khoir, Muhamad Sefri Nur (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to develop a practical self-defense training model based on Pencak Silat as an effort to prevent bullying among women aged 15–25 years in Dharmasraya Regency. The method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The developed product is a self-defense training manual. The validation results show that the developed model is highly valid, practical, and effective for use as a bullying prevention method. These results support the importance of mastering practical self-defense techniques to improve self-confidence, courage, and the ability to handle social conflict situations among young women.